Hakikat Alam Semesta dalam Perspektif Filsafat Pendidikan Islam - Ungu, Embun Sakara; Harry, Khairunnisa Dwi; Royani, Ida; Tanjung, Nur Khalizah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The universe or universe is other than Allah SWT, namely the firmament, sky, earth, stars, mountains and plains, rivers and valleys, plants, animals, humans, objects and the nature of things, as well as material and immaterial forms. He also said that some late Islamic scholars divided this world into four parts namely spirit, matter, space and time. Humans become one of the elements of the universe as new creatures whose mission is to prosper the universe and continue its development. shows that for people who are involved in the world of education, its connection with the process of creating the universe is that people who already have the potential, Allah SWT, to develop this potential cannot be realized spontaneously, but must be realized through a long process and stages in all their nature, means and tools, tools to help people get as much information as possible. Islamic education is that the universe was created for humans as something special to fulfill the mandate of Allah SWT as the caliph who guides, maintains, guards and transforms this nature into a way of life by obtaining various things to create this character. Based on this, humans know the essence of what is the purpose of creating the universe for themselves, which in essence makes humans become loyal and pious servants of Allah SWT. Keywords: Universe, Philosophy, and Islamic Education